Association of carotid atherosclerosis with brain tissue integrity and metabolic parameters in type 2 diabetes patients - Lim, Seung Hoon; Ryu, Chang-Woo; Tian, Yunan; Jun, Ji Eun; Park, Soonchan; Jeong, In-Kyung; Jahng, Geon-Ho (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is known to adversely impact brain health, leading to cognitive decline and brain tissue volume reduction. This study aimed to assess the damage to gray-white matter junction tissue volume (gwJTV) in T2DM patients with and without carotid artery plaques, and its association with various metabolic parameters.MethodsWe conducted a cross-sectional study involving 69 T2DM patients, employing three-dimensional T1-weighted MRI scans to measure brain tissue volumes, particularly gwJTV, and analyzing blood samples for metabolic parameters. Voxel-based (VBA) and region-of-interest (ROI) analyses of gwJTV were performed to evaluate the group difference with and without carotid artery plaques and to determine correlations to metabolic biomarkers.ResultsVoxel-based and region-of-interest analyses revealed that participants with carotid plaques had lower gwJTV than those without at the specific brain area. ROI results study further demonstrated positive associations between gwJTV and metabolic parameters such as AST, ApoB, and LDL, and negative associations with C-peptide, creatinine, and hsCRP.ConclusionOur findings suggest that gwJTV could be a valuable imaging biomarker for monitoring brain and vascular health in T2DM patients, particularly those affected by carotid atherosclerosis.